ANALISIS TERHADAP PUTUSAN NOMOR 19/PID.SUS-TPK/2018/PN PBR PADA TINDAK PIDANA KORUPSI PROYEK RUANG TERBUKA HIJAU DAN PEMBANGUNAN TUGU ANTI KORUPSI DI PROVINSI RIAU - Nadya Junyantani; Maria Maya Lestari; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
The corruption case in the case of decision Number 19/Pid.Sus-TPK/2018/PN Pbrthe application of the criminal sanctions given in this decision did not provide a deterrenteffect for the perpetrators and seemed selective. The DAS defendant was sentenced to 17months in prison and paid a fine of Rp. 50 million subsidiary 1 month in prison and paycompensation for state losses of Rp. 80 million. The judge's decision was lower than thedemands of the public prosecutor, namely 2 years in prison. The formulation of theproblem in the research are: 1) How is the application of criminal sanctions in thedecision Number 19/Pid.Sus-TPK/2018/PN Pbr?, 2) What are the judges' considerationsin the decision Number 19/Pid.Sus-TPK/2018/PN Pbr?.The results of this study are the application of criminal sanctions in the decisionNumber 19/Pid.Sus-TPK/2018/PN Pbr which is lighter than the prosecutor's demands.The sanctions given to the perpetrators do not show a deterrent effect on the perpetrators.The judge's consideration in the decision Number 19/Pid.Sus-TPK/2018/PN Pbr oncriminal acts of corruption in the green open space project and the construction of ananti-corruption monument in Riau Province juridically, the judge looked at the statutoryprovisions that were used as the basis for the indictment. In non-juridical terms, judgeslook at things that are aggravating and lighten punishments outside of juridical factors.Keywords: Analysis, Decision, Crime, Corruption